The Impact Of Formative Assessment On Teachers’ Practices - Belkhodja, Ibtissem; Bouazid, Tayeb (El Omda in Linguistics and Discourse Analysis, 2025)
Abstract Formative assessment plays a crucial role in the educational process by enabling teachers to identify learners’ strengths and weaknesses, thus allowing them to adjust their teaching approaches accordingly. This study investigates the impact of formative assessment on teachers' practices, focusing on how they utilize assessment data to modify their teaching methods and the factors influencing their use of such data. Employing a mixed-methods approach, the study collected both open and closed-ended questionnaire responses from 35 teachers (17 males and 18 females) from various secondary schools in District 2, North Setif, a city in East Algeria. The research revealed that teachers observed increased student involvement, reduced assessment-related stress, and a better understanding of educational goals. These findings suggest that formative assessment encourages teachers to adopt more participatory and learner-centered instructional strategies, enhancing the overall educational experience for students.